Unequal Error Protection Techniques Based on Wyner-Ziv Coding. (7th June 2009) - Liang Liang, Liang Liang; Salama Salama, Paul Paul; Delp Delp, Edward J. Edward J.
Abstract : Compressed video is very sensitive to channel errors. A few bit losses can stop the entire decoding process. Therefore, protecting compressed video is always necessary for reliable visual communications. Utilizing unequal error protection schemes that assign different protection levels to the different elements in a compressed video stream is an efficient and effective way to combat channel errors. Three such schemes, based on Wyner-Ziv coding, are described herein. These schemes independently provide different protection levels to motion information and the transform coefficients produced by an H.264/AVC encoder. One method adapts the protection levels to the content of each frame, while another utilizes feedback regarding the latest channel packet loss rate to adjust the protection levels. All three methods demonstrate superior error resilience to using equal error protection in the face of packet losses.